2022
DOI: 10.1039/d1cp05373f
|View full text |Cite|
|
Sign up to set email alerts
|

Lone pair driven anisotropy in antimony chalcogenide semiconductors

Abstract: The unique electronic and optical properties of Sb2S3 and Sb2Se3 are connected to their underlying crystal structures and chemical bonding.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
63
1
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(71 citation statements)
references
References 93 publications
6
63
1
1
Order By: Relevance
“…Ribbon formation is driven by the Sb lone pair, with ribbons stacked together by weak interactions. 11 According to our previous optimization using the HSE06 hybrid functional and D3 dispersion correction, 11 the calculated lattice parameters are 3.80/3.95 Å, 11.20/11.55 Å, and 11.39/11.93 Å for Sb 2 S 3 /Sb 2 Se 3 along the a , b , and c axes, respectively. Sb 2 X 3 are indirect band gap semiconductors with calculated indirect/direct band gaps of 1.79/1.95 eV and 1.42/1.48 eV, respectively, which are in reasonable agreement with previous experimental 1 5 , 27 − 29 and theoretical studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ribbon formation is driven by the Sb lone pair, with ribbons stacked together by weak interactions. 11 According to our previous optimization using the HSE06 hybrid functional and D3 dispersion correction, 11 the calculated lattice parameters are 3.80/3.95 Å, 11.20/11.55 Å, and 11.39/11.93 Å for Sb 2 S 3 /Sb 2 Se 3 along the a , b , and c axes, respectively. Sb 2 X 3 are indirect band gap semiconductors with calculated indirect/direct band gaps of 1.79/1.95 eV and 1.42/1.48 eV, respectively, which are in reasonable agreement with previous experimental 1 5 , 27 − 29 and theoretical studies.…”
mentioning
confidence: 99%
“…31 − 35 However, neither the structural dimensionality nor the electronic dimensionality of Sb 2 X 3 is 1D. 11 , 36 …”
mentioning
confidence: 99%
“…CdTe and GaAs are tetrahedral semiconductors that adopt the zincblende structure (space group F 43m). Sb 2 Se 3 and Sb 2 S 3 are layered materials (space group P nma), composed of one-dimensional [Sb 4 X 6 ] n ribbons with covalent metalchalcogen bonds within each ribbon and van der Waals interactions between ribbons [60][61][62][63][64][65] . Beyond these covalently-bonded crystals, we also studied four metal oxides (In 2 O 3 , ZnO, CeO 2 , TiO 2 ).…”
Section: Defect Suitementioning
confidence: 99%
“…4). This remarkable ability to distort likely stems from their soft, quasi-1D structure [61] , with van der Waals voids between atomic chains [69] (SI Fig. S5).…”
Section: Rebondingmentioning
confidence: 99%
“…To cut a long story short, we found that the dimensionality depends on the property you're interested in. So it might be that you have particular structural dimensionality, but then the bond strength, dielectric functions, effective masses each have their own anisotropy 20 . But one point we thought would be of direct relevance to this community is the carrier mobility, which shows that the conduction pathways in Sb 2 X 3 can be classified as 2D or 3D depending on the composition and carrier type 21 .…”
Section: Novel Semiconductorsmentioning
confidence: 99%